FDA Should Re-evaluate All mRNA Vaccines and Revoke Their Use Authorizations (The Short Version). - Wu, Jianqing (International Journal of Coronaviruses, 2022)
Drug industry, controlling medical publishers and large media promote flawed medicine for their revenues by systematically laundering medical knowledge in decades. They maintain and promote flawed research models and suppress disruptive discoveries, thereby precluding reform of medicine. In this study, I will deeply explore how the wrong life model, population-based research model, misused clinical trials, flawed statistical models, the symptom based research methods, binary disease classification, failure to address the massive vital organ capacities, failure to correct biases caused by expected delay in realizing side effects, and failure to address the interference effects of non-controllable factors affect the conclusions of “effectiveness and safety” for mRNA vaccines. I will directly analyze three studies that have been relied upon by FDA in approving mNRA use authorizations: one BNT162b2 effectiveness study published in NEJM, one booster shot study published in NEJM and a Seven Integrated Health Care Organizations study published by CDC. I will expose fatal flaws in the frequency risk concept, effectiveness rate, and hazard reduction ratios, and show why 3% death rate, 95% effectiveness rate and 90% mortality reduction are all meaningless and misleading, and should never have been used as treatment guidance. I will also examine common biases that can be easily practiced by sponsors’ researchers to alter conclusions in favor of approval. By relying on laundered medical “knowledge”, FDA has consistently failed to predict latent drug side effects for any drugs and vaccines in its history. FDA approved disastrous DES in 1941, Swine Flu vaccine in 1976, and mRNA vaccines in 2020. The vaccines are used to deliver short-term benefits on a small percent of persons at the costs of damaging health, causing deaths that could be avoided, and shortening lifespans for all people in the population. I thus urge FDA to reevaluate all mRNA vaccines and revoke their use authorizations.
Keywords: mRNA vaccines; use authorization; SARS-CoV-2; coronavirus; population vaccination; vaccine risks.